2021
DOI: 10.3389/fgene.2021.713793
|View full text |Cite
|
Sign up to set email alerts
|

Eight in One: Hidden Diversity of the Bagrid Catfish Tachysurus albomarginatus s.l. (Rendhal, 1928) Widespread in Lowlands of South China

Abstract: There is increasing evidence that species diversity is underestimated in the current taxonomy of widespread freshwater fishes. The bagrid species T. albomarginatus s.l. is mainly distributed in the lowlands of South China, as currently identified. A total of 40 localities (including the type locality), which covers most of its known range, were sampled. Molecular phylogenetic analyses based on concatenated mtDNA and nuclear genes recover nine highly supported lineages clustering into eight geographic populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…4), which is consistent with the previous study of Liu et al (2019). The traditional genera Leiocassis, Pseudobagrus, Pelteobagrus, and Tachysurus were not each monophyletic (Hardman 2005;Ku et al 2007;Liu et al 2019), but instead were grouped into Tachysurus as found in recent research (Cheng et al 2021;Shao et al 2021). Our results supported that the species in Leiocassis, Pseudobagrus, Pelteobagrus, and Tachysurus belong to the same genus, which by taxonomic priority should be Tachysurus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4), which is consistent with the previous study of Liu et al (2019). The traditional genera Leiocassis, Pseudobagrus, Pelteobagrus, and Tachysurus were not each monophyletic (Hardman 2005;Ku et al 2007;Liu et al 2019), but instead were grouped into Tachysurus as found in recent research (Cheng et al 2021;Shao et al 2021). Our results supported that the species in Leiocassis, Pseudobagrus, Pelteobagrus, and Tachysurus belong to the same genus, which by taxonomic priority should be Tachysurus.…”
Section: Discussionsupporting
confidence: 93%
“…However, the phylogenetic relationships between different genera of Bagridae are not well understood, such as the monophyly or the validity of Leiocassis , Pseudobagrus , Pelteobagrus , and Tachysurus . Recently, Leiocassis , Pseudobagrus , Pelteobagrus , and Tachysurus were classified into Tachysurus according to morphological analysis ( Cheng et al 2021 ; Shao et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Tachysurus sinensis is a senior subjective synonym of T. fulvidraco (Richardson, 1846) ( Ng and Kottelat 2007 ). Specimens, previously recognised as T. albomarginatus (Rendahl, 1928), from Lake Dongting represent an undescribed species, which was named as T. zhangfei ( Shao et al 2021 ). Possibly, Ru’s (2012) specimens, under the name of T. tenuis (Günther, 1873), from Lake Dongting were misidentified as it is hitherto known merely from the type locality, Chongming Island, Shanghai City ( Kottelat 2013 ; Cheng et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%